Artificial Intelligence in the Training of Economic Specialists - O. V. Gulina (Цифровая трансформация, 2025)
The article considers the feasibility of studying artificial intelligence in economic universities of the Republic of Belarus. The prerequisites for studying artificial intelligence technologies are formulated. The rationale for the need to introduce topics related to both the theoretical foundations of artificial intelligence and its potential for practical application for solving applied problems in the field of economics and management into the content of training future specialists in economics is provided. Using the example of the specialty “Economics and Management” of the profile “Economics and Management at an Industrial Enterprise”, proposals are formulated for amending the curriculum and content of academic disciplines aimed at developing the necessary competencies in the field of artificial intelligence in students for carrying out professional activities in the context of digital transformation of the economy. The key problems that hinder the practical implementation of the designated changes are identified, priority tasks for achieving the goal are formulated, and ways to solve them are proposed.